Non-Hodgkin lymphoma of vocal cord causing “pseudo-palsy” - Solav, Shrikant V.; Jagtap, Rajlaxmi R.; Savale, Shailendra V.; Bharadwaj, Reena; R., Chethana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Non epithelial lesion of vocal cord is identified as vocal cord palsy/ impaired movement without obvious mucosal ulceration. There are several nonepithelial lesions of vocal cord. Lymphoma, plasmacytoma, liposarcoma, lipoma, myxofibrolipoma, hemangioma, rhabdomyosarcoma are amongst the important differential diagnosis. These tumors occur in the submucosal layer of larynx and hence the mucosa appears intact at endoscopy. The lesions are typical non circumscribed, and invasion of adjoining structures helps in differentiating benign from malignant lesions. Presented here is a case of vocal cord (pseudo) palsy who underwent an 18F-fluorodeoxyglucose positron emission tomography computed tomography (18F-FDG PET CT) scan which revealed a hypermetabolic trans glottic soft tissue lesion. Histology confirmed the diagnosis of Extra-nodal High Grade Diffuse Large B Cell Non-Hodgkin lymphoma (DLBCL NHL).